PENGARUH KEPERCAYAAN DIRI TERHADAP KEMAMPUAN PUBLIC SPEAKING PADA MAHASISWA PENDIDIKAN SEJARAH UNIVERSITAS JAMBI - Dwi Nur Rahmadani; Anny Wahyuni; Ekawarna (Jurusan Pendidikan Ilmu Pengetahuan Sosial Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2021)
The aim of this study investigated is to describe the influence of self confidence on public speaking skills at History Education Students of Jambi University. Data obtained by distributing questionnaires and then analyzed quantitatively with a correlational research design. The results showed: there was an influence of self confidence on public speaking skills at History Education student of Jambi University because the value of thitung (16,960) > ttabel (1,65) and the significance probability value is 0,000 < 0,05. It means that the higher self confidence of history education students also makes the higher public speaking skills. The magnitude of the influence of self confidence on public speaking skills at History Education Students of Jambi University is 66,5% and the remaining 33,5% is influenced by other variables outside of this study. From the results of this study, it's recommended that lecturers no longer only focus on models, media, or learning methods but also have to pay attention to the psychology and mentality of students who can influence their attitude during class, so there’s no assumption that students who are less active when appearing in front of the class are students who are not good at learning